2020
DOI: 10.1111/odi.13338
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures of extracellular vesicles in oral fluids of periodontitis patients

Abstract: ObjectiveTo characterize extracellular vesicles (EVs) in gingival crevicular fluid (GCF) and saliva samples from healthy/gingivitis and periodontitis patients and correlate them with clinical inflammatory periodontal parameters.Material and MethodAn exploratory study, including 86 subjects, was conducted. Clinical and periodontal data were recorded, and oral fluid samples were obtained. EVs were precipitated by ExoQuick‐TC™ and characterized by nanoparticle tracking (NanoSight™), Western blot (WB), transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…The alteration of body fluid EV concentrations in pathological states has been described in both infectious and inflammatory models [ 35 , 36 ]. In patients with periodontitis, there is a higher concentration of EVs in gingival crevicular fluid, which correlates with the clinical inflammatory periodontal parameters [ 37 ]. A similar phenomenon is observed in patients with human African trypanosomiasis, where late stage patients have a higher concentration of EVs in cerebrospinal fluid when compared to early and intermediate stages, with these EVs also showing different functional properties such as altering astrocyte protein expression in vitro [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of body fluid EV concentrations in pathological states has been described in both infectious and inflammatory models [ 35 , 36 ]. In patients with periodontitis, there is a higher concentration of EVs in gingival crevicular fluid, which correlates with the clinical inflammatory periodontal parameters [ 37 ]. A similar phenomenon is observed in patients with human African trypanosomiasis, where late stage patients have a higher concentration of EVs in cerebrospinal fluid when compared to early and intermediate stages, with these EVs also showing different functional properties such as altering astrocyte protein expression in vitro [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an additional exploratory study, Chaparro et al detected the total concentration of EVs in gingival crevicular fluid (GCF) and saliva samples from patients with healthy gums/gingivitis or periodontitis. The authors did not detect significant differences in salivary EVs but found significant increases in the total concentration of medium/large EVs in GCF 22 . Since GCF consists of serum and locally generated components, including tissue breakdown products, inflammatory mediators, and antibodies in response to oral microorganisms, we speculate that there could be significant differences in GCF exosome levels between periodontitis patients and healthy individuals.…”
Section: Exosomes As Diagnostic Biomarkersmentioning
confidence: 78%
“…Periodontal ligament -derived stem cells were used to treat PD in humans (clinical trial identifier: NCT02523651). Apart from oral stem cells, other regenerative approaches such as the use of biomaterials, by themselves or used as scaffolds to load cells or drugs, extracellular vesicles, hold promising therapeutic future to repair and grow bone [69,70]. Nevertheless, additional studies are needed to determine the beneficial effects of using dental-derived stem cells and LLP2A-Ale for PDinduced bone loss.…”
Section: Discussionmentioning
confidence: 99%